2005
DOI: 10.1016/j.febslet.2005.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of circadian clock gene Clock in diabetes‐induced circadian augmentation of plasminogen activator inhibitor‐1 (PAI‐1) expression in the mouse heart

Abstract: Diabetes is associated with an excess risk of cardiac events, and one of the risk factors for infarction is the elevated-levels of plasminogen activator inhibitor-1 (PAI-1). To evaluate how the molecular clock mechanism is involved in the diabetes-induced circadian augmentation of PAI-1 gene expression, we examined the expression profiles of PAI-1 mRNA in the hearts of Clock mutant mice with streptozotocin-induced diabetes. Circadian expression of PAI-1 mRNA was blunted to low levels under both normal and diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 57 publications
(75 reference statements)
1
28
0
1
Order By: Relevance
“…These classical E-boxes are also involved in hypoxia-induced PAI-1 gene expression [15]. Recently, we showed that CLOCK-regulated transactivation of the PAI-1 gene plays an important role in diabetes-and obesity-induced hypofibrinolysis in mice [10,16]. Further elucidation of the regulation mechanisms of PAI-1 gene expression by circadian clock molecules should reveal the underlying mechanisms of not only circadian hemostatic changes but also various pathophysiologic conditions in vivo.…”
Section: Letters To Thementioning
confidence: 99%
“…These classical E-boxes are also involved in hypoxia-induced PAI-1 gene expression [15]. Recently, we showed that CLOCK-regulated transactivation of the PAI-1 gene plays an important role in diabetes-and obesity-induced hypofibrinolysis in mice [10,16]. Further elucidation of the regulation mechanisms of PAI-1 gene expression by circadian clock molecules should reveal the underlying mechanisms of not only circadian hemostatic changes but also various pathophysiologic conditions in vivo.…”
Section: Letters To Thementioning
confidence: 99%
“…Previous studies have shown an impact of CLOCK [31][32][33] and CRY 34 on the circadian oscillation of plasma PAI-1 and its mRNA. 15,35,36 Plasma levels of PAI-1 and tPA were measured to determine whether fluctuations in fibrinolytic activity related to the diurnal variation in the thrombotic response to injury.…”
Section: Clock Mutation But Not Endothelial Bmal1 Deficiency Altersmentioning
confidence: 99%
“…In contrast, UBP8, a component of the yeast SAGA complex, deubiquitylates H2B and stimulates transcription by enhancing Lys4 trimethylation of H3. Also notable is mammalian usp2; its mRNA cycles, and its transcription is under CLOCK/BMAL1 control (Oishi et al 2003(Oishi et al , 2005. USP2 was shown more recently to stabilize BMAL1 and CRY1 by deubiquitylation in mouse livers (Scoma et al 2011;Tong et al 2012).…”
mentioning
confidence: 99%